Single Cell Smart-Seq 3 RNA-Seq and Bulk Exome Seq from Breast Cancer Patients - Jun, Seong-Hwan; Toosi, Hosein; Mold, Jeff; Engblom, Camilla; Chen, Xinsong; O’Flanagan, Ciara; Hagemann-Jensen, Michael; Sandberg, Rickard; Hartman, Johan; Aparicio, Samuel; Roth, Andrew; Lagergren, Jens (Royal Institute of Technology, 2021)
Data Set Description
Single cell RNA sequencing (Samrt-Seq3) and Whole exome sequencing from multiple regions of individual tumors from Breast Cancer patients and also single cell RNA seq for two ovarian cancer cell lines.
The dataset contains raw sequencing data for various high-throughput molecular tests performed on two sample types: tumor samples from two breast cancer patients and cell lines derived from High-grade serous carcinoma Patients.

The breast cancer data comes from two patients: patient 1 (BCSA1) has two tumor regions A-B and patient 2 (BCSA2) has five regions(A-E). For a normal sample and each region from each patient Whole Exome Sequencing was performed using Twist Biosciences Human Exome Kit by the SNP&SEQ Technology platform, SciLifeLab, National Genomics Infrastructure Uppsala, Sweden. Also for each patient, EPCAM+ CD45- sorted cells from all the regions where sorted to a 384 well plate, and Smart-Seq3 libraries were prepared at Karolinska Institutet and sequenced at National Genomics Infrastructure Uppsala, Sweden.
The HGSOC cell-line data comes from OV2295R2 and TOV2295R cell lines described in Laks et al
Cell 2019 Nov 14; 179(5): 1207–1221.e22 doi: 10.1016/j.cell.2019.10.026 . The cell line Smart-Seq3 libraries were prepared from two 384 well plates at Karolinska Institutet and
sequenced at National Genomics Infrastructure Uppsala, Sweden.
Terms for accessThis dataset is to be used for research on intratumor heterogeneity and subclonal evolution of tumors. To apply for conditional access to the dataset in this publication, please contact datacentre@scilifelab.se (mailto:datacentre@scilifelab.se) .
Keywords: Plant cell and molecular biology; Animal cell and molecular biology; Other biomedical and clinical sciences not elsewhere classified; Genomics; Oncology and carcinogenesis not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi; Genetics and Genomics; Genetik och genomik; Medical Biotechnology; Medicinsk bioteknologi; Molecular Biology; Molekylärbiologi